Teacher Talk in Classroom Interaction Used by English Tutor in Mr. BOB English Course Kampung Inggris Pare - Dina Tri Fatmawati; Pratiwi Retnaningdyah; Slamet Setiawan (Edumaspul: Jurnal Pendidikan, 2022)
This paper aims to describe the teacher talk in classroom used by English tutor and the types of teacher talk in classroom interaction used by English Tutor in Mr. Bob English Course Kampung Inggris Pare. The subject of the research is the regular student who take Pronunciation program in Mr, Bob English Course. This research was a qualitative research, the data collection is by observation and voice recording. The researcher conduct the observation in classroom and recording when the teaching learning process. The result of the study showed that teacher talk in classroom interaction and the types of initiation and follow up used by teacher talk in classroom interaction. The type of initiation involved; questioning, invitation and direction, the type of follow up involved; inform, prompt, encouragement, criticizing, acknowledgement, and comment.